Balancing biological and economic goals in commercial and recreational fisheries: systems modelling of sea bass fisheries. (17th May 2021) - Tidbury, Hannah J; Muench, Angela; Lamb, Philip D; Hyder, Kieran
Abstract: The importance of social and economic factors, in addition to biological factors, in fisheries management is being increasingly recognised. However, exploration of trade-offs between biological, social, and economic factors under different sustainable catch limits for recreational and commercial fisheries is limited, especially in Europe. The European sea bass ( Dicentrarchus labrax ) is valuable and important for both commercial and recreational fisheries. Stocks have rapidly declined and management measures have been implemented, but trade-offs between social, biological, and economic factors have not been explicitly considered. In this study, a system dynamics model framework capturing biological and economic elements of the European sea bass fishery was developed and refined to incorporate a catch limit reflecting sustainable fishing with adjustable partition between recreational and commercial sectors, under low, medium, or high recruitment. Model outputs were used to explore the relative impact of different catch allocations on trade-offs between biological sustainability and economic impact when recruitment was limiting or not. Recruitment had a large impact on the fish population dynamics and the viability of the sectors. At high and moderate recruitment, management contributed to stock sustainability and sector economic impact, but recruitment is important in determining the balance between sectors.